The Performance Quality of Local Police Officers in Enforcing Local Regulations - Hamdan Muzakky; Siti Khumayah (CV. Media Digital Publikasi Indonesia, 2026)
Enforcement of local regulations (Perda) is one of the strategic functions of local governments in maintaining public order and community peace. The Civil Service police unit (Satpol PP), as a local government agency, plays a key role in enforcing these local regulations. However, in practice, the performance of Satpol PP offices in Cirebon City still faces various challenges, particularly those related to human resource management. This study aims to analyze the human resource management (HRM) functions of the Cirebon City Satpol PP, identify the inhibiting factors affecting them, and analyze the issues of staff shortages and mismatched backgrounds. This study employs a qualitative approach using a descriptive method. The theoretical framework draws upon Dessler’s (2017) theory of Human Resource management, specifically focusing on HR planning, training and development, and performance management. Data were collected through interviews and observations of Cirebon City Satpol PP personnel, then analyzed descriptively using triangulation techniques to ensure data validity. The results of the study indicate that the performance quality of Cirebon City Satpol PP personnel is not yet optimal, due to limited personnel numbers, low staff competence, and training and development programs that have not been fully implemented. Therefore, a planned and sustainable strengthening of human resource management is required to improve the effectiveness of local regulation enforcement.